The Influence of Accounting Information on Stock Prices of Food and Beverage Manufacturing Companies - Okeyo Oleyinka; Tyronni Chadire (Newinera Publisher, 2021)
The purpose of this study is to determine the effect of accounting information on stock prices of manufacturing companies in the food and beverage sub-sector This research takes place at the Stock Market office. The sample selection method in this study is a purposive sampling method with a total sample of 5 companies. The data collection techniques collect data on the company's financial statements during the research period. The data analysis method used was multiple regression with the help of SPSS for windows 25.00 software. The results showed that 1) Based on the results of data analysis, the coefficient values ​​of ROA, ROE, NPM, and EBIT showed an effect on stock prices simultaneously. 2) Based on the results of data analysis ROA, ROE, NPM partially significant effect on stock prices, while EBIT has no effect on stock prices of manufacturing companies in the food and beverage sub-sector on the Stock Market. 3) The most dominant variable that influences ROA, ROE, NPM and EBIT on stock prices of manufacturing companies in the food and beverage sub-sector on the Stock Market is the ROA variable